Factors affecting the performance of double chamber microbial fuel cell for simultaneous wastewater treatment and power generation - Khan, Maksudur R.; Amin, M. S. A.; Rahman, M. T.; Akbar, F.; Ferdaus, K. (Walter de Gruyter GmbH, 2013)
Electricity generation from the readily biodegradable organic substrate (glucose) accompanied by decolorization of azo dye was investigated using a two-chamber microbial fuel cell (MFC). Batch experiments were conducted to study the effect of dye and substrate concentration on MFC performance. Electricity generation was not significantly affected by the azo dye at 300 mg/L, while higher concentrations inhibited electricity generation. The chemical oxygen demand (COD) removal and decolorization of dye containing wastewater used in the MFC were studied at optimum operation conditions in anode and cathode, 57% COD removal and 70% dye removal were achieved. This study also demonstrated the effect of different catholyte solutions, such as KMnO4 and K2Cr2O7 on electricity generation. As a result, KMnO4 solution showed the maximum electricity generation due to its higher standard reduction potential.